Mutations in SARS-CoV-2 variants of concern link to increased spike cleavage and virus transmission - Escalera, Alba; Gonzalez-Reiche, Ana S.; Aslam, Sadaf; Mena, Ignacio; Laporte, Manon; Pearl, Rebecca L.; Fossati, Andrea; Rathnasinghe, Raveen; Alshammary, Hala; van de Guchte, Adriana; Farrugia, Keith; Qin, Yiren; et al. (Cell host & microbe, 2022)
SARS-CoV-2 lineages have diverged into highly prevalent variants termed “variants of concern” (VOCs). Here, we characterized emerging SARS-CoV-2 spike polymorphisms in vitro and in vivo to understand their impact on transmissibility and virus pathogenicity and fitness. We demonstrate that the substitution S:655Y, represented in the gamma and omicron VOCs, enhances viral replication and spike protein cleavage. The S:655Y substitution was transmitted more efficiently than its ancestor S:655H in the hamster infection model and was able to outcompete S:655H in the hamster model and in a human primary airway system. Finally, we analyzed a set of emerging SARS-CoV-2 variants to investigate how different sets of mutations may impact spike processing. All VOCs tested exhibited increased spike cleavage and fusogenic capacity. Taken together, our study demonstrates that the spike mutations present in VOCs that become epidemiologically prevalent in humans are linked to an increase in spike processing and virus transmission. [Display omitted] •The S:655Y mutation in SARS-CoV-2 enhances spike protein cleavage and fusogenicity•The S:655Y mutation increases transmissibility in vivo•S:655Y was able to outcompete ancestral S:655H in vivo•SARS-CoV-2 VOCs evolve to acquire an increased spike cleavage and fusogenic ability Escalera et al. show that spike mutation H655Y, which is present in SARS-CoV-2 variants gamma and omicron, enhances spike protein cleavage, cell-cell fusion, and transmission in the hamster model. Additionally, SARS-CoV-2 variants of concern are shown to have independently acquired mutations associated with a gain in spike cleavage and syncytia formation.